Complete mole coexisting with a normal fetus in a dichorionic diamniotic pregnancy: a case report - Maryanne Mwangi; Mjahid Hassan; Justus Wambugu Muthoni; Sikolia Wanyonyi (Journal of Medical Case Reports)
Abstract Introduction A molar pregnancy coexisting with a normal fetus is a very rare occurrence. It can present as a complete mole with a normal fetus or a partial mole with a normal fetus. There is paucity of data on optimal management of such patients who have this presentation, which mostly ends with a poor prognosis. Case presentation We present a case of 26-year-old woman of African descent, a para 1 + 0 gravida 2, who came with a compete molar pregnancy coexisting with a normal fetus in the second trimester and the complexity of her management. Patient presented in second trimester for an anomaly scan, in which the complete mole coexisting with a normal fetus was diagnosed. The molar pregnancy was also covering the cervical os. The patient was advised to terminate the pregnancy due to the risk of massive hemorrhage, but she was keen on continuing with the pregnancy. She was admitted two times with bleeding and in the last admission she also had chorioamnionitis, which warranted a hysterotomy at 25 weeks 1 day. Patient made a good recovery, unfortunately the neonate had an early neonatal death at a different facility due to respiratory complications. Conclusion In this case a patient with a normal fetus coexisting with a complete mole and complete previa was closely monitored, but a hysterotomy was done at 25 weeks 1 day gestation due to chorioamnionitis. The diagnosis was made by ultrasound, in which there was a snowstorm appearance of one of the gestational sacs while the other sac had a normal fetus. This is a rare entity that puts the doctor in a dilemma due to potential maternal and fetal complications. The take-home message is that a patient who presents with a complete mole and a coexisting normal fetus can be supported to a viability stage. Chorioamnionitis interfered with the continuation of this pregnancy.